RFRA and the hospitality industry in Indiana: political shocks and empirical impacts on Indianapolis' hospitality and tourism industry. Issue 3 (8th August 2016) - Webster, Craig; Yen, Chih-Lun (Alan); Hji-Avgoustis, Sotiris
Abstract : Purpose: Religious Freedom Restoration Act (RFRA) is a controversial bill passed by the State of Indiana and signed into law in March 2015. The purpose of this paper is to look into whether there is empirical evidence that the political shock of RFRA had a negative empirical impact upon the hotel industry in Indiana's major city, Indianapolis, and investigate how DMOs and other organizations in the tourism and hospitality industry worked in ways to counteract the threat of a great deal of loss of business caused by the national furor caused by the passing of the original bill in March 2015. Design/methodology/approach: To fully examine the impact of RFRA on hospitality business in Indiana, secondary data were used in this study. The researchers used the Trend Market report created by Smith Travel Research (STR) (2016b) with a focus on the greater Indianapolis area, which include Indianapolis South East, Indianapolis Central Business District, Indianapolis Airport/Speedway, Indianapolis North Loop, and Indianapolis small towns. In the Trend Market report, hotel operation performance results are listed including occupancy percentage, average daily rate, revenue per available room, supply, demand, and revenue. Findings: The findings from this investigation illustrate that there is no empirical reason to believe that the political shock of the RFRA controversy in Indiana in 2015 had a meaningful impact upon the hospitality and tourism industry in Indianapolis, despite concerns that it would make a big and negative impact upon the industry. While event planners may have a negative perception of the city of Indianapolis and the state, these perceptions do not seem to be enough to make a difference in terms of impacting upon the hospitality industry in Indianapolis. Originality/value: There are lessons that could be learned from this, as many states in the USA continue to pass similar laws to RFRA, laws that are perceived as being problematic for those in the lesbian, gay, bisexual, and transgender (LGBT) community. The most noteworthy lesson is that the passing of laws that seem to threaten people of the LGBT community will bring a national response and will likely be accompanied with threats that are economic in nature. There is a great deal of evidence to show that passing any legislation that may be interpreted as infringing upon the rights of members of the LGBT community will result in substantial responses that may be negative in nature.